Updatable Privacy-Preserving Reputation System based on Blockchain - Pilot, Matthias

A Formal Comparison of Advanced Digital Signature Primitives - Schürmann, Patrick

Designing Business Reputation Ecosystems — A Method for Issuing and Trading Monetary Ratings on a Blockchain - Hemmrich, Simon; Bobolz, Jan; Beverungen, Daniel; Blömer, Johannes (ECIS 2023 Research Papers)
Market transactions are subject to information asymmetry about the delivered value proposition, causing transaction costs and adverse market effects among buyers and sellers. Information systems research has investigated how review systems can reduce information asymmetry in business-to-consumer markets. However, these systems cannot be readily applied to business-to-business markets, are vulnerable to manipulation, and suffer from conceptual weak spots since they use textual data or star ratings. Building on design science research, we conceptualize a new class of reputation systems based on monetary-based payments as quantitative ratings for each transaction stored on a blockchain. Using cryptography, we show that our system assures content confidentiality so that buyers can share and sell their ratings selectively, establishing a reputation ecosystem. Our prescriptive insights advance the design of reputation systems and offer new paths to understanding the antecedents, dynamics, and consequences to reduce information asymmetry in B2B transactions.

Privacy-Preserving Collection and Evaluation of Log Files - Koch, Angelina

On the impossibility of surviving (iterated) deletion of weakly dominated strategies in rational MPC - Blömer, Johannes; Bobolz, Jan; Bröcher, Henrik

A Generic Construction of an Anonymous Reputation System and Instantiations from Lattices - Blömer, Johannes; Bobolz, Jan; Porzenheim, Laurens Alexander

Private Set Intersection using Third Generation FHE - Anonymous, A.

Rational Models in Cryptography Applied to Matching - Anonymous, A.

Modelling and Proving Security for a Secure MPC Protocol for Stable Matching - Vahle, Ella

Bringing Structure to Structure-Preserving Signatures: Overview, Implementation and Comparison of Selected SPS Schemes - Siek, Hanna

On Transforming Lattice-Based Cryptography to the Ring Setting - Kramer, Paul

Evaluating database systems relying on secure multiparty computation - Anonymous, A

Cost of Privacy-preserving SMPC Protocols for NN-Based Inference - Anonymous, A

Lattice Revocation Mechanisms - Lohse, Jan

Privacy-Preserving Cryptography: Attribute-Based Signatures and Updatable Credentials - Eidens, Fabian

Comparison of Open Source Software in Quantum Computing from the Perspective of Software Development - Anonymous, Anonymous

A Detailed Survey and Comparison of the Selected Homomorphic Encryption Libraries - Anonymous, Anonymous

Analysis of an Interactive Lattice Based Aggregated Signature Scheme - Beckmann, Marvin

Cryptimeleon: A Library for Fast Prototyping of Privacy-Preserving Cryptographic Schemes - Bobolz, Jan; Eidens, Fabian; Heitjohann, Raphael; Fell, Jeremy

Issuer-Hiding Attribute-Based Credentials - Bobolz, Jan; Eidens, Fabian; Krenn, Stephan; Ramacher, Sebastian; Samelin, Kai (Cryptology and Network Security)